High Speed Internet and the Widening Gender Gap in Adolescent Mental Health: Evidence from Hospital Records - Esther Arenas-Arroyo; Daniel Fernández-Kranz; Natalia Nollenberger (Institute of Labor Economics (IZA), 2022)
Increases in mental health problems among adolescents have been concurrent with increased use of digital media, with bigger changes among girls after the mid-2010s. This study exploits exogenous variation in the deployment of optic fiber across Spanish provinces between 2007 and 2019 to analyze the effect of access to high-speed Internet (HSI) on hospital discharge diagnoses of behavioral and mental health cases among adolescents. We find a positive and significant impact on girls but not on boys. Exploring the mechanism behind these effects, we show that HSI increases addictive Internet use and significantly decreases time spent sleeping, doing homework, and socializing with family and friends. Girls again power all these effects. We find no evidence of an increase in online bullying. Finally, we show that fiber expansion harms the quality of the relationship between fathers and daughters, especially when that relationship suffers from a previous conflict. Our results help explain the observed widening gender gap in mental health among adolescents and are robust to various sensitivity tests.
Keywords: J13; J16; I10; I12; I18; H31; L86; 330; high-speed internet; adolescents; mental health